Development of a slurry injection technique for continuous fibre ultra-high temperature ceramic matrix composites. Issue 14 (November 2019) - Baker, B.; Rubio, V.; Ramanujam, P.; Binner, J.; Hussain, A.; Ackerman, T.; Brown, P.; Dautremont, I.
Abstract: A simple and effective slurry injection method for producing dense and uniform ultra-high ceramic matrix composites from preforms of high fibre density was developed. As this method is based on slurry injection the homogeneity is not constrained to small preform sizes; dense components of high fibre volume can be produced in theoretically any size and shape. Samples produced by this method demonstrated high and consistent densities, with the injection method obtaining densities an average 27% higher and 87% lower in variability when compared to conventional vacuum impregnation. Tomography demonstrated no bias in the ceramic powder distribution for samples produced by injection, whereas samples produced by vacuum impregnation alone displayed poor powder penetration to the centre of large samples. The new approach yielded composites that were as strong and/or more consistent in strength compared to vacuum impregnation. Thermo-ablative testing demonstrated significant improvements in protective capability for materials produced by this route.